2020
DOI: 10.12688/f1000research.21790.1
|View full text |Cite
|
Sign up to set email alerts
|

How scientific research changes the Vietnamese higher education landscape: Evidence from social sciences and humanities between 2008 and 2019

Abstract: Background: In the context of globalization, Vietnamese universities, whose primary function is teaching, there is a need to improve research performance. Methods: Based on SSHPA data, an exclusive database of Vietnamese social sciences and humanities researchers’ productivity, between 2008 and 2019 period, this study analyzes the research output of Vietnamese universities in the field of social sciences and humanities. Results: Vietnamese universities have been steadily producing a high volume of publications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 33 publications
(21 reference statements)
0
11
0
Order By: Relevance
“…Figure 2 below provides the distribution of the above two categories. In 2016, there were 11 STEM publications, which was two times higher compared to SSH publications (5). In 2018, the number of STEM publications (38) was 1.4 times higher than SSH.…”
Section: Fig 1 the Number Of The X University's Scientific Productsmentioning
confidence: 92%
“…Figure 2 below provides the distribution of the above two categories. In 2016, there were 11 STEM publications, which was two times higher compared to SSH publications (5). In 2018, the number of STEM publications (38) was 1.4 times higher than SSH.…”
Section: Fig 1 the Number Of The X University's Scientific Productsmentioning
confidence: 92%
“…Therefore, it is extremely necessary to propose a criteria and measures for domestic scientific journals to access international publishing standards as well as improve the capacity of Vietnamese researchers. In a number of studies related to improving the quality of international publications of scientists in Vietnam, the issue of improving the capacity of ranking research journals appeared in the works of Chung et al(2019), Cuong, Loc, Trung, & Trung (2020), Ho et al (2019) Hoang et al (2020), Hung (2016), Nguyen et al (2020), Trang et al (2020), Trung, Linh, Phuong, Toan, & Hoang (2020). Most authors have confirmed the trend of increasing the quantity and quality of research in general and research in the field of educational science in Vietnam.…”
Section: Introductionmentioning
confidence: 98%
“…Likewise, this argument is underpinned by a preceding report that claimed that disparities in higher education participation in South Asian countries were disturbing (T. L. H. Nguyen, 2013; T. H. T. Nguyen et al, 2020; UNESCO, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…P. 23) and formulate strategies to support the majority of women faculties who are struggling with “publish or perish” higher education policy forces. Accordingly, Vietnam is one of the model countries in East Asia, where women have a load of family burden, which emerged from centuries of the country’s socio-cultural stereotype (T. H. T. Nguyen et al, 2020; Q.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation